EXPLORING THE DETERMINANTS OF PROENVIRONMENTAL BEHAVIOUR IN ECO-TOURISM: A CASE STUDY OF VISITORS TO THE AYAZINI RUINS - YAYLA, İsa; BAYDENİZ, Erdem; ÇILGINOĞLU, Hakkı (Economics of Agriculture, 2023)
This study aims to determine the pro-environmental behaviour influencing factors of tourists within the scope of eco-tourism. The population of the study consists of tourists visiting Ayazini Ruins. In the study, the data were collected using a questionnaire form with a convenience sampling method. 406 questionnaires were administered to the participants. The data were analyzed in the Smart PLS statistical program, and the structural equation model was used to analyze the data. Functional, social, and emotional value significantly positively affects environmental consciousness; conditional value does not positively influence environmental consciousness. Moreover, environmental consciousness significantly positively affects the green image, last chance experience, psychological ownership towards the environment, and pro-environment attitudes. Besides this green image, last chance experience, psychological ownership towards the environment, and pro-environment attitudes significantly positively affect pro-environment behaviour.